(untitled) (Journal of Hama University, 2022)
This study aimed to identify the extent of the impact of enabling leadership behaviors on the dimensions of the organization’s leadership represented in (seizing opportunities (proactive), innovative, taking risks, and offensive). The researcher relied on the descriptive analytical method and studied a cluster random sample of hospital staff in the case of the study The study concluded that there is a positive effect of the elements of enabling leadership in the elements of proactivity and innovation as one of the elements of entrepreneurship, despite the difference of this effect, which ranged between good and moderate to some extent, and there are no fundamental differences in the impact of enabling leadership behaviors in promoting entrepreneurship at Al-Assad University Hospital according to the difference of personal characteristics. The results showed that the trend towards the application of enabling leadership contributes to the development and strengthening of the success factors of the organization’s leadership elements and works to enhance them, and that the most influential factor is the promotion of opportunities for participation in decision-making